2016
DOI: 10.3233/bsi-160144
|View full text |Cite
|
Sign up to set email alerts
|

An infrared spectroscopic blood test for non-small cell lung carcinoma and subtyping into pulmonary squamous cell carcinoma or adenocarcinoma

Abstract: Abstract. BACKGROUND:Lung cancer is the leading cause of death for male and female cancer patients alike. Early diagnosis improves prognosis. A blood test would be a valuable support. OBJECTIVE: Infrared spectroscopy provides a label-free biochemical fingerprint of a sample. A study was conducted on 161 patients with initial cancer suspicion to identify and verify spectral biomarker candidate patterns to detect non-small cell lung carcinoma (NSCLC). METHODS: Blood serum and plasma samples were analysed with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Thus, recent reports detailing the detection of specific disease in dried blood serum or plasma samples, such as the detection of cancer of the brain , prostate , bladder , lung , breast ovary , liver and bile duct , may have to be re‐evaluated in terms of their claims of detecting a specific disease. Rather, these reports may have detected a disease‐induced change in the AGR that may be much larger than signals expected for specific disease markers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, recent reports detailing the detection of specific disease in dried blood serum or plasma samples, such as the detection of cancer of the brain , prostate , bladder , lung , breast ovary , liver and bile duct , may have to be re‐evaluated in terms of their claims of detecting a specific disease. Rather, these reports may have detected a disease‐induced change in the AGR that may be much larger than signals expected for specific disease markers.…”
Section: Introductionmentioning
confidence: 99%
“…Tester) we provide a robust methodology to make it easier to test different pre- The Random Forest (RF) machine learning algorithm is widely used in many different fields of research, including cheminformatics, [10,11] bioinformatics, [12], and ecology, [13]. Within the field of biomedical spectroscopy, RF has been used in the annotation of lung cancer subtypes [14] and in the diagnosis of nonsmall cell lung carcinoma, [15] urinary bladder cancer, [16], hyperlipidemia [17], and brain tumours [7]. RF has proven to be a robust and accurate technique for developing spectral diagnostic models, giving excellent classification results without over-fitting.…”
Section: Prffect (Pre-processing and Random Forest Feature Extraction Cmentioning
confidence: 99%
“…It was suggested that FTIR in sputum cells showed high sensitivity and specificity in diagnosing the disease within a small range of significant wave numbers [10] . Another study was performed on 161 patients with initial cancer suspicion with the FTIR analysis of blood sample to identify non-small cell lung carcinoma (NSCLC) [43] . Biochemical differences between blood samples of control and lung carcinoma patients were detected in the spectra and an accuracy of 80% was achieved in separation of squamous cell and adenocarcinoma patients.…”
Section: Lung Cancermentioning
confidence: 99%